2020
DOI: 10.1177/1533033820916191
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Radiomics in Breast MRI: A Review

Abstract: Breast cancer has been a worldwide burden of women’s health. Although concerns have been raised for early diagnosis and timely treatment, the efforts are still needed for precision medicine and individualized treatment. Radiomics is a new technology with immense potential to obtain mineable data to provide rich information about the diagnosis and prognosis of breast cancer. In our study, we introduced the workflow and application of radiomics as well as its outlook and challenges based on published studies. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 111 publications
(175 reference statements)
0
60
0
Order By: Relevance
“…Radiogenomics can potentially evaluate the entire tumor load with the possibility of providing a non-invasive diagnosis and to closely monitor the characteristics of the lesions [75][76][77][78][79]. The combination of quantitative radiomics features with histological, clinical, and genomic data may represent a valid possibility for clinicians to develop patient-centered treatments [72,[80][81][82].…”
Section: Texture Analysis and Prognosis-focus On Breast Cancermentioning
confidence: 99%
“…Radiogenomics can potentially evaluate the entire tumor load with the possibility of providing a non-invasive diagnosis and to closely monitor the characteristics of the lesions [75][76][77][78][79]. The combination of quantitative radiomics features with histological, clinical, and genomic data may represent a valid possibility for clinicians to develop patient-centered treatments [72,[80][81][82].…”
Section: Texture Analysis and Prognosis-focus On Breast Cancermentioning
confidence: 99%
“…Therefore, more MRI radiomics studies were reported than ultrasound, mammography, and 18F FDG PET/CT (34). MRI radiomics was shown to provide better discrimination than conventional parameters for the diagnosis of breast cancer (23,24). Mammography radiomics analysis has also been performed in several diagnostic studies (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) based radiomics study has been widely applied for medical applications. The method allows for high-throughput extraction of quantitative features from radiographic images (18), and it has been shown as a feasible approach for diagnosis of breast cancer using mammography (19)(20)(21)(22) and MRI (23)(24)(25). However, the combined model using different imaging modalities was rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, radiomics is an appealing technique in research but it has not been fully applied yet in the clinical setting but multidisciplinary and translational studies are still required, gather the amount of data needed to implement radiomics on a wide scale. As it is difficult to acquire consistent imaging and acquire uniform results that can be applied in clinical practice [ 89 ] (due to imaging acquisition from different machines, varied technical parameters and slice thickness and diverse reconstruction algorithms), some techniques to deal with multicentric data have been proposed such as ComBat [ 90 ]. However, radiomics models based on transparency of methodologies and developed using standardized acquisition techniques and high-quality data can overcome confounders arising from differences among centers’ workflows.…”
Section: What Next?mentioning
confidence: 99%